Fever duration, peak temperature and associated symptoms in Chinese adults with SARS-CoV-2 infection: a cross-sectional study - Ye, Yang; Xin, Xiyan; Du, Xinying; Bai, Yunjing; Shen, Hongbo (Frontiers in Medicine, 2025)
IntroductionAlthough the COVID-19 pandemic has passed, we still lack a comprehensive understanding of its fever-related characteristics. This study aims to elucidate the unique fever characteristics exhibited by Chinese SARS-CoV-2 patients, providing insights into the fever patterns of COVID-19 and enhancing our understanding of fever caused by viral infections.MethodsA descriptive study was conducted using an online questionnaire administered through a web-based survey platform from December 19, 2022, to January 5, 2023. Data pertaining to the demographic features and fever dynamics of SARS-CoV-2-infected individuals were collected and analyzed.ResultsThe study cohort consisted of 555 adult individuals presenting with fever, comprising 157 males (28.3%) and 398 females (71.7%), with a mean age of 39.8 ± 12.7 years. The average duration of fever was 2.5 ± 1.6 days, with a peak temperature recorded at 38.7 ± 0.7 °C. Notably, a negative correlation was discerned between peak fever temperature and age, while in female participants, fever duration displayed a positive correlation with age. Patients with underlying comorbidities, particularly those with lupus erythematosus, exhibited lower peak temperatures. Predominant symptoms reported during febrile episodes encompassed headache, cough, general malaise, and myalgia, while post-fever symptoms predominantly comprised cough, sputum production, nasal obstruction, and sore throat.ConclusionAge may be an important factor influencing both the duration of fever and peak body temperature in SARS-CoV-2 infected individuals, while gender-specific variations appear to be limited. COVID-19 patients demonstrated noticeable heterogeneity in symptom manifestations both during the febrile phase and after fever resolution.